Acute cholecystitis: Diagnosis and treatment according to contemporary literature - Tarigan, M. Fadillah (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2026)
Background: Acute cholecystitis remains a leading cause of emergency visits in patients with gallstone disease and requires an integrated approach including clinical assessment, imaging, severity grading, antibiotic therapy, and timely source control. Method: The Tokyo Guidelines 2018 and WSES guidelines provide a standardized diagnostic framework and recommend early laparoscopic cholecystectomy as the treatment of choice when the patient is physiologically fit. Ultrasonography is the first-line imaging modality, though its sensitivity is moderate; therefore, CT, MRI/MRCP, or hepatobiliary scintigraphy may be required in equivocal or complicated cases. Results: Early laparoscopic cholecystectomy during the index admission is the definitive treatment, with subtotal cholecystectomy or alternative strategies considered when safe dissection is not feasible. Antibiotics are essential in the acute phase but should not replace definitive source control. Gallbladder drainage (percutaneous or endoscopic) remains an important option for high-risk surgical patients but should be applied selectively rather than as a routine alternative to surgery. Conclusion: A practical, streamlined algorithm integrating disease severity, patient condition, and institutional expertise is recommended to optimize management.